The Pattern of Antidumping and Other Types of Contingent Protection - Bown, Chad P. (World Bank, Washington, DC, 2012)
Many of the major economies in the multilateral, rules-based trading system find themselves in a situation in which their applied tariff rates are quite close to the tariff binding levels that form their legal commitments at the World Trade Organization (WTO). This implies that they cannot simply raise applied tariff rates to respond to domestic industry demands for additional trade barriers to protect them from imports. One of the fundamental and potentially WTO-legal ways in which national governments can respond to domestic industry calls for additional protection from imports is by resorting to trade 'remedy' policy instruments such as antidumping, safeguards, and countervailing duty (anti-subsidy) policies. This note, which describes newly collected data made available through the World Bank-sponsored global antidumping database, reports on the combined use of such policies, comprehensively collected across the major WTO member economies.